Measuring Sustainability: Financial Proxies To Measure Environmental And Social Performance - Chong, Pey Chinn (2011)
defining business-societal relations, current measurement of corporate social, and environmental performance, five approaches that have the potential to be used by companies to measure its sustainability performance with a form of financial proxies, eco-efficiency, true cost, sustainable value, SROI, Eco-Asset Valuation, benefits of measuring sustainability performance using financial proxies, merits limitations, and challenges of the approaches, framework to assess and select suitle approach, challenges in measuring environmental, and social performance using financial proxies